Dispositivos tecnológicos de mediação, hibridização cultural e processos comunicativos na Reserva Indígena de Dourados e entre os Ayoreo do Paraguai - Rivas, Elton Domingues (2012)
This paper aims the studying of the ownership of mediation technological devices by the Guarani Indians and of the Terena at Dourados Indigenous Reservation ( Mato Grosso do Sul BR) and similar experiences among the Ayoreo people, inhabitant of the Paraguayan Chaco. The question that motivates the thesis is whether it is possible to seize the occasions and how the culture transits between cultural traditions/original fragments and the new elements from indigenous contact with the contemporary world-post-industrial-informational. Using as methodological base the documentation of those devices , especially comparing approaches and differences during daily situations observed in the surveyed subjects, the analysis of transit is based in the following cases: 1) the technological means have streamlined their roles by the generation of contents of hybrid dimension and are privileged instruments of mediation, appropriation and re-evaluation of signs, in addition to adjustments for the incorporation and production of meaning on different and unrelated repertoires; 2) cultural identity is transformed by the results of polyphonies and polysemies that are part of various connections that the subjects are subjected to, composed by assimilations, influences, contagion and contaminations under constant construction. The theoretical basis of semiosphere concept formulated by Yury Lótman, which contemplates the idea of frontieres between semiotic spaces, fundamental concept to the understanding the production of communicative environments; the nature of the image as communicative sign and the construction of visibilities from the technical sector, total or partially, concepts proposed by Norval Baitello Junior and Lucretia Ferrara, in addition to the concepts of hybridism of Nestor g. Canclini and mediation of Jesús Martín-Barbero